Password Authentication for multicast host using zero knowledge Proof - Seetha Ranganathan; R. Saravanan (Institute of Advanced Engineering and Science, 2015)
The password which is a more secure and valuable data should be highly protected from eavesdropper. This paper presents how password required for authentication of members of group communication is securely delivered by the source or initiator of the group. The password delivery uses zero knowledge proof and sent to the group member in an encrypted format using cipher block mode encryption. The password delivered is a One Time Password which can be used for certain amount of time in order to ensure a highly secure communication environment among the group.